Dental anomalies in permanent teeth and the associated etiological factors among fifteen years-old students in Basrah city - Al-Sheraydah, Nadia Azzam; Al-Dahan, Zainb (Journal of Baghdad College of Dentistry, 2017)
ABSTRACT Background: Dental anomalies of teeth are major issue that contributes to dental problems encountered in general practice. The aim of this study is to measure the prevalence of dental anomalies and the associated etiological factors among 15 years old students in Basrah city –Iraq. Materials and methods: The total sample composed of 1000 students (435 males and 565 females) from urban area selected randomly from different high schools in the city. Diagnosis of dental anomalies were recorded by present or absent, diagnosis and recording of enamel defects were done according to the criteria of WHO (1997). Results: The prevalence of hypodontia was 4.6%, Females have higher prevalence than males (5.8% females and 3.0% males), talon cusp prevalence was 37.0% (males 38.6% and females 35.8%), the prevalence of microdontia was 1.4% (males were equal to females 1.4%), the prevalence of supernumerary teeth, fusion, macrodontia and gemination was 0.8%, 0.7%, 0.1% and 0.1% respectively. The prevalence of enamel defects was 30.5%, demarcated opacities prevalence was 23.8%, it is the most prevalent type of enamel defects (males 20.5% and females 26.4%) followed by diffuse opacities 9.1% then enamel hypoplasia 0.4%. Conclusion: This study revealed that secondary school students have dental anomalies, some of them with high prevalence, while other has very low prevalence